Congress of Neurological Surgeons Systematic Review and Evidence-Based Guideline for the Management of Patients With Positional Plagiocephaly: The Role of Physical Therapy. Issue 5 (1st November 2016) - Baird, Lissa C.; Klimo, Paul; Flannery, Ann Marie; Bauer, David F.; Beier, Alexandra; Durham, Susan; Lin, Alexander Y.; McClung-Smith, Catherine; Mitchell, Laura; Nikas, Dimitrios; Tamber, Mandeep S.; Tyagi, Rachana; et al.
Abstract: BACKGROUND: Evidence-based guidelines are not currently available for the treatment of positional plagiocephaly and, in particular, for the use of physical therapy for treatment. OBJECTIVE: To answer the question: "does physical therapy provide effective treatment for positional plagiocephaly?" Treatment recommendations are created based on the available evidence. METHODS: The PubMed and the Cochrane Library were queried using MeSH headings and key words relevant to the objective of this systematic review. Abstracts were reviewed, after which studies meeting the inclusion criteria were selected and graded according to their quality of evidence (Classes I-III). Evidentiary tables were constructed that summarized pertinent study results, and recommendations were made based on the quality of the literature (Levels I-III). RESULTS: Three studies met criteria for inclusion. Two randomized, controlled trials (Class I and Class II) and 1 prospective study assessing plagiocephaly as a secondary outcome measure (Class III) were included. CONCLUSION: Within the limits of this systematic review, physical therapy is significantly more effective than repositioning education as a treatment for positional plagiocephaly. There is no significant difference between physical therapy and a positioning pillow as a treatment for positional plagiocephaly. However, given the American Academy of Pediatrics' recommendation against soft pillows in cribs to ensure a safe sleeping environment for infants, physical therapy must be recommended over the use of a positioning pillow. The full guidelines document can be located at https://www.cns.org/guidelines/guidelines-management-patients-positional-plagiocephaly/Chapter_4 .